Full 1H and 13C NMR spectral assignment of conjugated valerolactone metabolites isolated from urine of black tea consumers by means of SPE‐prepLC–MS–LC–MS‐NMR. (19th March 2019) - de Roo, Niels; Wilmsen, Sanne M. J.; Mihaleva, Velitchka V.; Jacobs, Doris M.; van Duynhoven, John P. M.
Abstract: The health benefits of black tea have been linked to polyphenol metabolites that target specific modes of action in the human body. A major bottleneck in unravelling the underlying mechanisms is the preparative isolation of these metabolites, which hampers their structural elucidation and assessment of in vitro bioactivity. A solid phase extraction (SPE)‐preparative liquid chromatography (prepLC)–MS–LC–MS‐NMR workflow was implemented for preparative isolation of conjugated valerolactone metabolites of catechin‐based polyphenols from urine of black tea consumers. First, the urine was cleaned and preconcentrated using an SPE method. Subsequently, the clean urine concentrate was injected on a preparative LC column, and conjugated valerolactones were obtained by MS‐guided collection. Reconstituted fractions were further separated on an analytical LC column, and valerolactone fractions were collected in an MS‐guided manner. These were reconstituted in methanol‐ d 4 and identified and quantified using 1D and 2D homo‐ and hetereonuclear NMR experiments (at a field strength of 14.1 T), in combination with mass spectrometry. This resulted in the full spectral 1 H and 13 C NMR assignments of five conjugated valerolactones. These metabolites were collected in quantities of 8–160 μg and purities of 70–91%. The SPE‐prepLC–MS–LC–MS‐NMR workflow is suitable for isolating metabolites that occur at sub‐μM concentrations in a complex biofluid such as urine. The workflow also provides an alternative for cumbersome and expensive de novo synthesis of tea metabolites for testing in bioactivity assays or for use as authentic analytical standards for quantification by mass spectrometry. Abstract : Implementation of workflow for preparative isolation of conjugated valerolactones from urine Full 13 C and 1 H NMR spectral assignment of five conjugated valerolactones Perspectives for automated preparative isolation of metabolites from urine for full heteronuclear assignment, use as authentic standards and bioactivity testing